Osteoarthritis Care and Risk of Total Knee Arthroplasty Among Medicare Beneficiaries: A Population‐Based Study of Regional Covariation. Issue 12 (28th October 2021) - Ward, Michael M.
Abstract : Objective: To examine health care utilization among patients with knee osteoarthritis (OA) and assess whether utilization differs among residents of regions with high and low rates of total knee arthroplasty (TKA). Methods: This was a retrospective cohort study of US Medicare beneficiaries with knee OA enrolled from 2005 to 2010. Health care utilization data for knee complaints, including rates of physician visits, physical therapy, knee injections, and arthroscopy, were abstracted from claims files until time of TKA or the end of the study in 2015. Utilization was compared among beneficiaries who lived in regions with high or low rates of TKA. Results: Among 988, 570 beneficiaries with knee OA, 327, 499 (33.1%) underwent TKA during follow‐up (median 5.6 years). Higher frequency of visits for knee complaints was associated with increased risk of TKA, whereas physical therapy, specialist care, and intraarticular treatments were associated with lower risk of TKA. Frequency of TKA varied from 26.4% in the lowest regional TKA rate quintile to 42.1% in the highest regional TKA rate quintile. Rates of physician visits, physical therapy, specialist care, and treatment with intraarticular injections varied inversely with regional TKA rate quintile. For example, 32.5% of beneficiaries in the lowest region quintile and 23.6% in the highest region quintile underwent physical therapy. Across all quintiles, physical therapy was associated with lower TKA rates. Conclusion: Dedicated nonsurgical OA care was infrequently used to treat elderly Americans with knee OA. Nonsurgical care was more common in regions with low TKA rates, suggesting reciprocal emphasis on medical treatment compared to surgical treatment across regions.